The place of Balance in rhetorics and the âinvestigation of its status in Anvariâs divan - مهری گلشنی راد (مطالعات زبانی و بلاغی)
This article deals with balance and its variety in âAnvariâs divan. Balance is one of the verbal devices in ârhetorics that creates more music in a poem and results in its âcharm and charisma. Balance forms from the contrast âbetween the balanced and sometimes parallel rhymes. In this âstudy, we observe other kinds of balance in the Anvariâs âdivan, which have been dealt with in few rhetorical books âand by that we mean the balance in two consecutive distiches, âin the way that the first verse of the first distich is in balance âwith the first verse of the second distich , and the second âverse of the first distich is in balance with the second verse âof the second distich. The third type is also the case that only âthe first two verses or the second two verses in the two âconsecutive distiches are in balance with each other. In this âstudy, we tried to explain them by providing evidence for âeach of these types.The results suggest that this literary âdevice and its variants in Anvariâs divan are among the most âfrequent literary arrays which were used. And since Anvari is âa panegyrist poet, he took the advantage of using this literary âdevice to have more impact on his audience. â